ATRIAL FIBRILLATION AND ISCHEMIC HEART DISEASE: HOW TO COMBINE ANTIPLATELET AND ANTICOAGULANT THERAPY, DEPENDING ON THE CLINICAL SITUATION? - D. A. Napalkov; A. A. Sokolova; A. V. Rodionov (Рациональная фармакотерапия в кардиологии, 2016)
Up-to-date European approaches to the management of patients with atrial fibrillation (AF) after acute coronary syndrome and/or percutaneous coronary interventions are considered. Features of antithrombotic therapy in the early (hospital) and the delayed periods (up to 1 year after acute ischemic events) are discussed. The authors briefly present subanalysis of ARISTOTLE study, which compares the efficacy and safety of apixaban with these of warfarin in patients with atrial fibrillation and a history of ischemic heart disease.